Oral plasmablastic lymphoma in a HIV-positive woman: Literature review and case report - Nuernberg, Marta Aparecida Alberton; Lopes-Santos, Gabriela [UNESP]; Furuse, Cristiane [UNESP]; Montalli, Victor Ângelo Martins; Helena Theodoro, Leticia [UNESP]; Cristine Tjioe, Kellen [UNESP] (Wiley, 2021)
We provide a comprehensive review of plasmablastic lymphoma (PBL) in HIV-positive patients and report a case of HIV-associated oral plasmablastic lymphoma. We complied and discussed demographic, clinical, histopathological, immunohistochemical, therapeutic and prognostic features of 105 cases reported in English and Spanish literature. The inclusion criteria were documented cases of confirmed PBL of the oral cavity in HIV-positive patients. Only cases with definitive microscopic diagnosis of PBL and description of HIV infection were included. Reports with insufficient clinical information of the patients were excluded. The literature review revealed 105 cases of HIV-associated oral PBL in 46 published manuscripts. In addition, we reported the case of an aggressive oral PLB arising in a 30-year-old HIV-positive female. This study provides a comprehensive review of clinical and microscopical landscape of PBL. Additionally, our data suggest that case reports should be more rigorous and detailed about the clinical findings, in order to facilitate the understanding of the clinical presentation pattern of oral PBL.
Keywords: human immunodeficiency virus; immunohistochemistry; non-Hodgkin's lymphoma; oral cancer; oral plasmablastic lymphoma